2006
DOI: 10.1088/0953-2048/19/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of HTS composite tapes to pulsed currents

Abstract: Dynamic voltage-current characteristics of an HTS Ag/BiSCCO composite tape are studied both experimentally and theoretically. The tape is subjected to pulsed currents with different shapes and magnitudes and voltage traces are measured using the four-point method with different locations of potential taps on the sample surface. Clockwise and anticlockwise hysteresis loops are obtained for the same sample depending on the location of the potential taps. The dynamic characteristics deviate substantially from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This electric field also moves the 'normal conducting' electrons that are always present at finite temperatures T > 0. In equation ( 1) putting the electric field E ∝ ω one gets equation (5). Due to the flux creep in the superconductor it takes a finite time for the flux to diffuse into the sample.…”
Section: Thin Stripmentioning
confidence: 99%
See 1 more Smart Citation
“…This electric field also moves the 'normal conducting' electrons that are always present at finite temperatures T > 0. In equation ( 1) putting the electric field E ∝ ω one gets equation (5). Due to the flux creep in the superconductor it takes a finite time for the flux to diffuse into the sample.…”
Section: Thin Stripmentioning
confidence: 99%
“…They have found that the peak current at high frequency can surpass the dc critical current in a superconducting tape. Meerovich et al [5,6] have studied the dynamic response of HTS tapes to pulsed currents of different shapes. They have found that dynamic V -I characteristics deviates substantially from dc characteristics, especially in the low voltage range (1-10 μV cm −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…(8) A frequency dependent critical current was introduced by Rhyner [34], and was further developed in [35,36]. Reference [37] has tried several different theoretical approaches to account for the frequency dependence of magnetic susceptibility, and finally ended up using an empirical equation which resembled the π/2 rule [33] for spin-glass systems (χ = −π/2(dχ /d ln(ω))) at some specific magnetic field.…”
Section: Frequency Dependencementioning
confidence: 99%
“…All the integral equations we proposed in the previous paragraphs cannot be analytically solved and have to be worked out by means of some ad hoc numerical scheme, essentially based on substituting the integrals with finite sums and on transforming the equations in systems of algebraic equations (see, for instance, [16]). Even so, another more practical way can be followed by using a general purpose FE commercial package (in our case COMSOL Multiphysics version 3.4 [17]) that allows implementing parameter-depending integrals.…”
Section: Integral Equations Solutionmentioning
confidence: 99%